2018
DOI: 10.1002/mbo3.595
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of fungi in hot desert sands

Abstract: The fungal community of six sand samples from Saudi Arabia and Jordan deserts was characterized by culture-independent analysis via next generation sequencing of the 18S rRNA genes and by culture-dependent methods followed by sequencing of internal transcribed spacer (ITS) region. By 18S sequencing were identified from 163 to 507 OTUs per sample, with a percentage of fungi ranging from 3.5% to 82.7%. The identified fungal Phyla were Ascomycota, Basal fungi, and Basidiomycota and the most abundant detected clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 54 publications
3
27
0
Order By: Relevance
“…Microbial diversity in Sabkha and desert was earlier investigated and well documented ( Murgia et al, 2019 , Jaouani et al, 2014 ). Soil is known as a rich habitat with different types of microbial communities.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Microbial diversity in Sabkha and desert was earlier investigated and well documented ( Murgia et al, 2019 , Jaouani et al, 2014 ). Soil is known as a rich habitat with different types of microbial communities.…”
Section: Resultsmentioning
confidence: 96%
“…Recent studies reported the isolation of hyaline fungi, like Myrothecium and Fusarium , from the soil in the northern region of Saudi Arabia together with the common Aspergillus and Penicillium ( Hemida and Abdel-Sater, 2016 ). A large fungal biodiversity including Ascomycota , basal fungi, and Basidiomycota, Dothideomycetes , Pezizomycetes , and Sordariomycetes were isolated from Jordanian and Saudi Arabian deserts ( Murgia et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our study, in metagenomics analysis of rhizosphere fungal communities in arid and semi-arid ecosystems, Suleiman et al [47] and Vargas-Gastélum et al [48] also showed a high relative abundance of Ascomycota and Basidiomycota phyla in the rhizosphere of Vachellia pachyceras and plants from Valle de Las Palmas, respectively. While the composition of fungal communities in the bulk also show a high abundance of these phyla [49][50][51], so their presence would be associated with type of soil and climate which is decisive for the rhizospheric microbiome assembly process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two novel halophilic fungi isolated from a cave in the Coastal Range of the Atacama Desert were designated as Aspergillus atacamensis and Aspergillus salisburgensis (Martinelli et al ). Extensive fungal diversity has been recorded in Middle East desert sand (Murgia et al ) and three novel fungal species, Diverispora omaniana, Septoglomus nakheelum and Rhizophagus arabicus, were recorded from a desert in Oman (Symanczik et al ).…”
Section: Desertsmentioning
confidence: 99%